Community engagement and chronic viral hepatitis public health interventions: a systematic review, meta-analysis, and complementary crowdsourcing open callResearch in context - Yifan Li; Eneyi Kpokiri; Dalia Elasi; Rongrong Sheng; Keying Wang; Hayley Conyers; Ye Zhang; Danjuma K. Adda; Philippa C. Matthews; Thomas Fitzpatrick; Joseph D. Tucker; Dan Wu (EClinicalMedicine)
Summary: Background: Chronic viral hepatitis causes a high burden of morbidity and mortality, especially in low- and middle-income countries (LMICs). While community engagement, which involves stakeholders in addressing health-related issues, has shown promise to enhance hepatitis outcomes, evidence on its impact remains limited. To summarize the current state of knowledge on this topic we performed a systematic review and a crowdsourcing open call. Methods: A parallel mixed-methods approach was used in this study. The systematic review included publications that evaluated a community-engaged intervention, reported chronic viral hepatitis outcomes, included a comparator group, and were published in English up to 12 March 2025. A random-effects model was used to pool the overall effect of the community-engaged interventions on hepatitis outcomes. To ensure innovative ideas from LMICs were included, we organized a complementary crowdsourcing open call using the WHO/TDR practical guide. Thematic analysis identified key themes in the crowdsourced submissions. Findings: 35 studies were included in the systematic review, and 28 crowdsourced submissions were analyzed. In both the systematic review and open call, community-engaged interventions included peer-based interventions, community health workers, interactive educational programs, and patient advocacy. The meta-analysis, predominantly of studies from high-income countries, found community-engaged interventions significantly improved HBV vaccine completion (RR 1.59, 95% CI 1.15–2.19; I2 = 88.10%), HBV/HCV test uptake (RR 2.33, 95% CI 1.78–3.06; I2 = 99.10%), HBV and HCV linkage to chronic viral hepatitis care (RR 1.96, 95% CI 1.46–2.64; I2 = 96.20%), HBV/HCV treatment adherence (RR 1.14, 95% CI 1.03–1.27; I2 = 0%), and HCV sustained virologic response (RR 1.50, 95% CI 1.23–1.83; I2 = 93.90%). Open call submissions, largely from LMICs, highlighted community-led interventions where patients led community-based organizations to advocate for improved access to hepatitis care. Interpretation: Findings underscored the importance of community engagement in chronic viral hepatitis service delivery across the care continuum. Implementing community-engaged interventions can enhance chronic viral hepatitis elimination efforts. Funding: National Natural Science Foundation of China.